On being open-minded, wholehearted, and responsible: a review and synthesis exploring factors enabling practitioner development in reflective practice. Issue 6 (2nd November 2021) - Marshall, T.; Keville, S.; Cain, A.; Adler, J. R.
ABSTRACT: Although reflective practice is valued in learning and professional development, there are a wide range of contrasting definitions making it difficult to firstly understand what reflection is and subsequently how to apply this concept in specific working contexts. This study aims to bridge this gap in the literature by enquiring into and seeking an understanding of the factors that enable the process of reflection by synthesising insights from a variety of publications across professional contexts. The analytical process involved initial coding and focussed coding, supplemented by constant comparison and memo writing. Article text was fragmented, sorted, and integrated to develop a thematic structure that was used to organise and integrate the subsequent narrative. Analysis resulted in 3 higher order themes: triggers for reflection, conducive contextual and attitudinal factors, and epistemology. The resulting article represents the product of an enquiry seeking to understanding the factors that enable the process of reflection.